Synthetic Alloys: Synthetic Crystals of Silver with Carbon: 3D Epitaxy of Carbon Nanostructures in the Silver Lattice (Adv. Funct. Mater. 30/2015). (10th August 2015) - Salamanca‐Riba, Lourdes G.; Isaacs, Romaine A.; LeMieux, Melburne C.; Wan, Jiayu; Gaskell, Karen; Jiang, Yeping; Wuttig, Manfred; Mansour, Azzam N.; Rashkeev, Sergey N.; Kuklja, Maija M.; Zavalij, Peter Y.; Santiago, Jaime R.; et al.
Abstract : As shown by L. G. Salamanca‐Riba and co‐workers on page 4768, 3D‐epitaxy of carbon in silver is acheived by electrocharging assisted bulk processing. The carbon and silver bond covalently when a high current is applied to a mixture of liquid silver and particles of activated carbon. Upon solidification, graphitic structures form within the metal with an epitaxial orientation with the silver lattice. Image courtesy of Jiaqi Dai from the University of Maryland.